1) h(t) = t2 + 5t; t = −1, t = 2

2) af(z) = 5 − 4z2; z = −2, z = 0

3) f(x) = x3 − 5x2; x = 0, x = 10

4) f(x) = x + x4; x = −3, x = 5

5) f(x) = 5x2; x = 3, x = 3 + h

6) f(x) = 3 − x2; x = 6, x = 6 + h

I'm not absolute about this but i think your just supposed to substitute.For example....

h(t)=t2+5t turns into -1=-1(2)+5(2) simplifies to -1=-2+10 =-1=8

srry if incorrect.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up